Pharmacokinetics of intravenous and nebulized gentamicin in critically ill patients. (26th June 2018) - Boisson, Matthieu; Mimoz, Olivier; Hadzic, Mirza; Marchand, Sandrine; Adier, Christophe; Couet, William; Grégoire, Nicolas
Abstract: Objectives: Optimal dosing for nebulized gentamicin is unknown. We compared the pulmonary and systemic pharmacokinetics (PK) of gentamicin following intravenous and nebulized administration in mechanically ventilated patients. Methods: Twelve critically ill male patients with ventilator-associated pneumonia received a 30 min intravenous infusion of 8 mg/kg gentamicin, followed 48 h afterwards by the same dose nebulized. Blood samples were collected immediately before and until 24 h after intravenous and nebulized administration; mini-bronchoalveolar lavages (mini-BALs) were performed at 3 and 7 h or 5 and 10 h (six patients each) after each intravenous and nebulized administration. The PK analysis was conducted using a population approach. Results: After intravenous administration, concentrations of gentamicin measured in epithelial lining fluid (ELF) were very variable, and overall in the same range of magnitude (from 0.3 to 28 mg/L) as in plasma. After nebulization, gentamicin concentrations were much higher (∼3800-fold) in ELF than in plasma. The average systemic bioavailability of nebulized gentamicin was estimated to be 5%, with considerable inter-individual variability. Compared with intravenous administration, after nebulization the exposure (expressed as AUC) to gentamicin was 276-fold greater in ELF and 18-fold lower in plasma. Conclusions: Compared with intravenous administration, nebulization of gentamicin in patients with ventilator-associated pneumonia provides higher pulmonary concentrations and lower systemic concentrations but the inter-individual variability is large.